A Study on Distribution of Water Quality Parameters in Potable/Ground Waters of Visakhapatnam Coastal Region with Multivariate Factor Analysis - Murty, V.V.K.P.L.N.; V.S. Machiraju, P.; Shyamala, P.; Vinod Kumar, A. (Asian Journal of Chemistry, 2021)
Chemical components of the earth crust influence the ground water quality. In addition, anthropogenic activities also contribute in deteriorating the quality of ground waters and contaminate the water sources. In present study, 22 water samples were collected from the potable/ground water sources in south coastal region of Visakhapatnam district, India during pre- and post-monsoon seasons and characterized for physico-chemical parameters viz., pH, electrical conductivity (EC), total dissolved solids (TDS), salinity, oxidation reduction potential (ORP), dissolved oxygen (DO), temperature, total hardness (TH), total alkalinity (TA), bicarbonate, carbonate, chloride, fluoride, sulphate, nitrate, phosphate, calcium, magnesium, sodium and potassium. The distribution of parameters was explained by Box-Whisker plot. Further Piper diagrams were drawn to identify the geochemical expressions between the parameters. Multivariate factor analysis was used to assess the degree of factor loadings and to identify the group of parameters influencing the variance of different water quality parameters. The analytical data indicated that majority of water samples in the study area have higher concentration of TDS, TH, TA, Ca2+, Mg2+, Na+, Cl−, HCO3− and F−.